Innovation and its role in industrial excellence and the development of logistics services in KSA - Nasrulddin, Vivian Mohammed Saleh; Alidrisi, Tharaa Hassan Omar (Journal of Economic, Administrative and Legal Sciences, 2023)
The study aimed to identify the role of innovation in the development of industrial excellence and the performance index of logistics services in the Kingdom of Saudi Arabia for the period 2010-2021. The two models of multiple linear regression analysis have been described, the first includes the industrial excellence index as a dependent variable, while the second includes the performance index of logistics services as a dependent variable. The two models also include the independent variables related to innovation, which were selected based on previous studies and researchers’ judgments, which are: the number of ICT industry establishments, the percentage of technology exports out of total industrial exports, the percentage of spending on research and development of GDP, and the number of patents For residents, the balance of foreign investment. By identifying the variables and hypotheses to be tested, descriptive tests were conducted, and the general trend of the variables was identified, by the statistical program E-views. With regard to the first model, the study showed a direct relationship between the Industrial Excellence Index and the number of ICT industry establishments, and the percentage of technological exports. The study also showed that the percentage of spending on research and development did not affect the industrial excellence index. As for the second model, the study showed an inverse relationship between the performance index of logistics services and the percentage of spending on research and development, and the number of patents. The study also showed that the percentage of technological exports did not affect that indicator.